A mini review developing an integrated delivery system model using a lean approach - Zahiruddin, Mohd Zain; Norazlianie, Sazali; Ramli, Junid (Universiti Malaysia Pahang, 2025)
Delivery system services are a crucial component of the logistical infrastructure supporting Malaysian citizens, particularly in public service delivery. With the rise of digital technology, traditional information dissemination methods have been replaced by advanced digital systems that enhance interactivity, efficiency, and cost-effectiveness. This shift underscores the importance of developing Integrated Delivery System Models (IDSM) to ensure citizens receive timely, accurate information for informed decision-making. This mini review examines the application of lean principles to improve the efficiency and effectiveness of IDSM in Malaysia’s public service sector. Lean methodologies, which focus on reducing inefficiencies and optimizing processes, are explored as a framework to enhance transparency, accessibility, and system performance. Existing delivery system models and theories are reviewed to highlight the need for holistic systems thinking in addressing inefficiencies and overcoming the challenges of conventional delivery methods. Furthermore, the role of public policy in supporting lean integration is critically analyzed, with an emphasis on relational database systems to enable data-driven decision-making. These systems play a vital role in enhancing accuracy and operational efficiency, particularly in applications like general elections.This review presents a step-by-step framework for developing a lean-based IDSM, offering practical insights for policymakers and public administrators. By aligning social innovation, open governance, and technological advancements, this study aims to contribute to the design of a sustainable, citizen-centric public service delivery model that meets Malaysia’s evolving needs.